PENGARUH E-WOM DAN BRAND TRUST TERHADAP PURCHASE INTENTION (Studi Kasus Pada Konsumen Go-jek di Yogyakarta) - Azmi Hadi (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This research, is expected to prove influence between variable namely e-wom as electronic word of mouth ) brand so and purchase intention. In this research used a quantitative approach namely by spreading the questionnaire to respondents users go-jek in yogyakarta.An analyzer used the test the assumption classical and test t with the results of research suggests that all the variables affect each other.